Effectiveness of Coronary Artery Disease Health Education among the patients of Coronary Artery Disease in Tertiary Cardiac Centre - Dhungana, Suraksha; Prajapati, Dipanker; Malla, Rabi; Dangol, Prati Badan; Soti, Binita; Thakuri, Shanta Singh; Khadka, Januka; Kaphle, Sangita; Koirala, Vidya Joshi; Adhikari, Chandra Mani (Nepalese Heart Journal, 2024)
Background and Aims: Secondary prevention of coronary artery disease is vital in preventing the future cardiac events. Inadequate knowledge of the disease is related to non-compliance with the treatment therapy which directly results in disease progression and its complication. The objective of this study is to assess the effectiveness of health education about coronary artery disease among the patients of coronary artery disease in a tertiary cardiac centre. Methods: A quantitative, prospective, interventional research design was designed to collect the data by non-probability convenience sampling method. Patients diagnosed with coronary artery disease and admitted in different wards of Shahid Gangalal National Heart Centre were included. Data was collected from July 2022 to December 2022 in three phases: prior to health education; within 24 hours of health education and after 3 months. A semi structured face to face interview was used to collect data from the patients, which was then filled in the web-based questionnaire and appropriate statistical methods were used for analysis. Results: A total of 167 patients were enrolled during the study period. Only 145 (86.8%) patients completed the 3rd phase of data collection. There was a significant improvement in patients’ overall knowledge (P value; <.01) as well as knowledge regarding medical (P value; <.01), coronary artery disease risk factors (P value; <.01), exercise (P value; <.01), nutrition (P value; <.01) and psychological risk (P value; <.05). There was a significant improvement (P value; <.01) related to behavior related characteristics like smoking, tobacco consumption, alcohol consumption and physical activity. However, correlation between health behaviors and post intervention knowledge showed a non-significant weakly positive relation of knowledge with education (r=.081), whereas there was non-significant weakly negative relation with physical activity (r=-.0126). Conclusion: The educational intervention has significant improvement in level of knowledge and change in behavior pattern among the patients of coronary artery disease. This study demonstrates that targeted health education programs can lead to significant improvements in knowledge and behavior among coronary artery disease patients, potentially reducing hospital readmission rates and promoting better long-term disease management.